A heating glove based on thermal insulation aerogel

By using a double-layer thermally insulated aerogel structure braided with surface-modified boron nitride-based aerogel fiber, and the introduction of flame retardants of nano-hydroxyapatite and magnesium hydroxide, the shortcomings of existing heating gloves in flame retardant, flexibility and waterproof performance are solved, and the effects of efficient warmth and safety protection are achieved.

CN118716722BActive Publication Date: 2025-03-14SHENZHEN EIGDAY HEATING LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411106653.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-03-14
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

Existing thermally insulated aerogel heating gloves have shortcomings in flame retardant, flexibility and waterproof performance, resulting in a lack of safety and thermal insulation performance.

Method used

A double-layer thermally insulated aerogel structure woven with surface-modified boron nitride-based aerogel fiber is combined with flame retardant of nano-hydroxyapatite and magnesium hydroxide to improve the flame retardant, flexibility and waterproof performance of gloves.

Benefits of technology

Significantly improves the thermal insulation, flame retardant and waterproof performance of gloves, ensuring efficient warmth and safety protection in extreme cold environments while maintaining the flexibility and durability of gloves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118716722B_ABST
    Figure CN118716722B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electric heating gloves, and provides a heating glove based on thermal insulation aerogel, including a glove body, which is composed of an outer layer, an upper thermal insulation aerogel layer, a lower thermal insulation aerogel layer, a heating layer, a thermal conductive insulation layer and an inner layer from the outside to the inside; a power slot with an open zipper is provided on the back of the hand, a rechargeable power supply is built in, the heating layer is connected by a wire, and a temperature control module is integrated, which supports four-speed adjustment of off, low temperature, medium temperature and high temperature, and a charging interface is provided for easy charging with an external power supply. The aerogel layer of the present invention breaks through the limitation that traditional aerogel can only insulate. The upper layer of thermal insulation aerogel integrates thermal insulation, moisture resistance, anti-fouling and flexibility, which improves the thermal insulation performance, cleaning convenience and wearing comfort of the electric heating gloves in a humid environment; the lower layer of thermal insulation aerogel is both thermally insulating, flame retardant and highly flexible, and is in close contact with the heating layer, which enhances the heating efficiency and safety, while maintaining the flexibility of the gloves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrically heated gloves, and in particular to a heating glove based on thermal insulation aerogel. Background Art

[0002] In the bitter winter, gloves are a necessity for daily protection, and their warmth retention is particularly critical. Traditional gloves, whether they are made of natural cotton, wool, or synthetic PU leather, can resist the cold to a certain extent, but under extreme low temperature conditions, their warmth retention ability is inadequate, and they are often lacking in waterproofness, windproofness, and comfort. Against this background, electric heating gloves came into being. By integrating high-efficiency heating elements and precise temperature control systems, and innovatively incorporating heating and insulation layer designs, they have greatly improved the comprehensive performance and practical value of gloves. In recent years, the leap forward in materials science has led aerogel, a new type of nanomaterial, into the public eye. Aerogel, known for its ultra-low density and excellent thermal insulation properties, shows broad application potential.

[0003] At present, although a lot of progress has been made in thermal insulation aerogel, there are still some shortcomings. (1) The flame retardant performance still needs to be further improved to meet the requirements of more stringent use environments. For example, the Chinese patent with publication number CN212212820U discloses an aerogel electric heating glove. Although the design is advanced, the thermal insulation layer aerogel lacks flame retardant properties. Once a short circuit occurs in the internal circuit of the glove, it may quickly evolve into a fire risk, seriously threatening the safety of use. (2) The realization and maintenance of flexibility is still one of the technical difficulties. For example, the Chinese patent with publication number CN116807113A discloses a cold-proof electric heating glove. Although it innovatively integrates aerogel powder into polyester staple fiber to construct an insulation layer, this design is prone to gradually weakening the insulation effect during long-term wear due to the insufficient flexibility of the powder itself, affecting the wearing experience and warmth retention efficiency. (3) The lack of waterproof performance is also a major challenge. Although aerogel performs well as an insulation material, in actual wear, if it cannot effectively block the intrusion of external moisture, it may cause the heating element to short-circuit, reducing the safety and service life of the gloves. Therefore, the thermal insulation aerogel of the current heating gloves still faces many challenges in terms of flame retardancy, flexibility and waterproofness. In order to fill this technical gap, it is necessary to develop a new type of heating gloves so that the thermal insulation aerogel of the heating gloves has excellent flame retardancy, flexibility and waterproofness to meet the needs of high-performance heating gloves. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a heating glove based on thermal insulation aerogel to solve the problem that the current thermal insulation aerogel has insufficient performance in terms of flame retardancy, flexibility and waterproofness.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A heating glove based on thermal insulation aerogel comprises a glove body, wherein the glove body comprises an outer layer, an upper thermal insulation aerogel layer, a lower thermal insulation aerogel layer, a heating layer, a thermal conductive insulating layer and an inner layer from the outside to the inside; the outer layer, the upper thermal insulation aerogel layer, the lower thermal insulation aerogel layer, the heating layer, the thermal conductive insulating layer and the inner layer are all connected together by stitches; a power supply receiving slot with an open sealing zipper is provided at the back of the hand of the glove body, the built-in power supply is placed in the power supply receiving slot and connected to the heating layer through a wire, a temperature regulating module for adjusting the degree of heating is provided in the wire, the temperature regulating module is provided with an off mode and a heating mode, the heating mode has three gears of low temperature, medium temperature and high temperature, the built-in power supply is a rechargeable power supply, and one end of the rechargeable power supply is also provided with a charging interface for connecting to an external power supply.

[0009] Furthermore, the upper thermal insulation aerogel layer is formed by weaving surface-modified boron nitride-based aerogel fibers through warp and weft; the diameter of the surface-modified boron nitride-based aerogel fibers is 0.2 to 1 mm; and the thickness of the upper thermal insulation aerogel layer is 0.6 to 3 mm.

[0010] Furthermore, the surface modified boron nitride-based aerogel fiber is made of the following raw materials in parts by weight: 20 to 45 parts of boron nitride-based aerogel fiber, 150 to 180 parts of polyethylene glycol 1000, 20 to 30 parts of polydimethylsiloxane, 2 to 3 parts of dicumyl peroxide, and 60 parts of ethanol; the mass ratio of the polydimethylsiloxane to dicumyl peroxide is 10:1.

[0011] The present invention relates to an upper layer aerogel material in an electric heating glove woven from surface-modified boron nitride-based aerogel fibers, which exhibits multiple excellent properties. First, in terms of thermal insulation performance, the aerogel layer significantly blocks the gas heat conduction path by virtue of its high porosity and nanoscale pore size characteristics, and the unique pore structure of the woven layer further enhances this thermal insulation effect. Secondly, in terms of flexibility and mechanical properties, the boron nitride-based aerogel fiber is composited with boron nitride and polyimide. The imide ring in the polyimide molecular chain gives the material excellent mechanical strength and flexibility, and the use of the fiber woven structure ensures the flexibility and foldability of the material. Furthermore, the inherent insulation of boron nitride effectively improves the overall insulation performance of the aerogel. In addition, the fiber surface is modified by polydimethylsiloxane, and the hydrophobic groups in its molecular chain form strong intermolecular interactions with boron nitride and polyimide, which not only optimizes the interface bonding, but also constructs a hydrophobic protective layer, thereby significantly improving the moisture resistance and anti-pollution ability of the material. At the same time, polydimethylsiloxane modification also gives the fiber high chemical stability, excellent insulation performance and good air permeability, greatly broadening the application scope of the material. In summary, the surface-modified boron nitride-based aerogel fiber woven composite material has achieved functional integration in multiple dimensions such as thermal insulation, mechanical strength, and surface properties. It is applied to the aerogel layer of electric heating gloves to achieve multiple functions such as thermal insulation, lightweight, high flexibility, moisture resistance and anti-pollution. It performs well in terms of warmth retention, comfort, flexibility and durability, and is particularly suitable for various cold environments such as winter outdoor operations, cold storage work, and high-altitude expeditions, showing broad application potential and prospects.

[0012] Furthermore, the lower thermal insulation aerogel layer is woven from thermal insulation and fire-resistant gas gel fibers through warp and weft, and the diameter of the thermal insulation and fire-resistant gas gel is 0.4-1.2 mm; the thickness of the lower thermal insulation aerogel layer is 1-4 mm.

[0013] Furthermore, the heat-insulating and flame-retardant gas gel fiber is made of the following components by weight: 20 to 45 parts of 4,4'-diaminodiphenyl ether, 20 to 45 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide, 4 to 8 parts of nano-hydroxyapatite, and 3 to 8 parts of magnesium hydroxide; the mass ratio of the 4,4'-diaminodiphenyl ether to the 3,3',4,4'-biphenyltetracarboxylic dianhydride is 1:1.

[0014] Furthermore, the preparation method of the nano hydroxyapatite is as follows: by weight, 20 to 40 parts of 0.2 mol / L calcium nitrate aqueous solution are adjusted to a pH of 9 to 11 with 10% ammonia water, and then 15 to 25 parts of 0.2 mol / L diammonium hydrogen phosphate aqueous solution are added thereto, and then stirred evenly at room temperature for 24 to 36 hours. During the stirring process, 10% ammonia water is required to maintain the pH of the mixed solution at 10. After the stirring is completed, the mixture is filtered, and then the filter residue is washed 3 times with deionized water. Each washing requires that the filter residue is completely submerged with deionized water, and then the washed filter residue is completely dried in a vacuum drying oven at room temperature to finally obtain nano hydroxyapatite.

[0015] Furthermore, the average particle size of the nano-hydroxyapatite is 40 to 80 nm.

[0016] The heat-insulating, flame-retardant gas gel fiber woven gloves designed by the present invention have a heat-insulating aerogel layer below that integrates multiple excellent properties, achieving a significant improvement in performance. This layer uses an aerogel material with a highly porous structure, which effectively isolates the conduction and transfer of heat with its extremely low thermal conductivity, showing an excellent heat-insulating effect. At the same time, the outer layer uses a fiber-woven polyimide material, which not only gives the gloves the characteristics of high strength, heat resistance and chemical corrosion resistance, but also ensures the flexibility and durability of the gloves. More importantly, the introduction of nano-hydroxyapatite and magnesium hydroxide as flame-retardant additives can quickly form a protective layer under high temperature conditions, preventing the spread of combustion caused by accidental short circuits in electric heating gloves, and significantly improving the flame-retardant properties of the gloves. The combined effect of these characteristics makes the gloves excellent in heat insulation, durability and safety, providing all-round protection for the wearer.

[0017] In the design of the electric heating gloves of the present invention, the upper and lower insulating aerogel layers, through exquisite synergy, jointly construct a comprehensive protection system that integrates heat preservation, heat insulation, flame retardancy, lightness, flexibility and durability. The upper insulating aerogel layer, with its high porosity and nanoscale pore size characteristics, effectively blocks the conduction and convection of heat. In addition, the composite advantages of boron nitride and polyimide not only enhance the insulation effect, but also give the material excellent mechanical strength, flexibility and insulation properties. The surface modification of polydimethylsiloxane further improves the material's moisture resistance, anti-pollution and chemical stability, so that the gloves can still maintain excellent performance in complex and changeable environments. The lower insulating aerogel layer serves as another solid line of defense. Its highly porous aerogel material effectively isolates the intrusion of external heat, forming a double-layer insulation barrier with the upper aerogel layer, greatly enhancing the insulation effect of the gloves. At the same time, the addition of the fiber braided polyimide outer layer not only enhances the structural strength and durability of the gloves, but also provides good flexibility, ensuring that the wearer can feel comfortable and at ease in various activities. More importantly, the flame retardant mechanism of nano-hydroxyapatite and magnesium hydroxide builds another line of defense in the lower insulating aerogel layer, which can respond quickly to unexpected situations such as high temperature or short circuit, prevent the spread of combustion, and ensure the safety of the wearer. Therefore, the synergistic effect of the upper and lower layers of aerogel materials not only achieves multiple barriers to heat transfer, but also takes into account the flexibility, durability, safety and comfort of the gloves, making the electric heating gloves of the present invention an ideal choice for workers in cold environments, with extremely high application value and market prospects.

[0018] Furthermore, the outer layer is a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, and its preparation method is: after 3 to 6 parts of heptadecafluorodecyltrimethoxysilane and 80 to 100 parts of methanol are evenly mixed, 15 to 25 parts of polyurethane fiber membrane are completely immersed therein, and the immersion time is 10 to 16 hours, and then the impregnated polyurethane fiber membrane is taken out and dried in a vacuum drying oven at 50 to 60°C for 20 to 28 hours to obtain the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane.

[0019] Furthermore, the preparation method of the polyurethane fiber membrane is as follows: by weight, 10 to 18 parts of polyurethane, 3 to 8 parts of aluminum oxide nanoparticles and 80 to 120 parts of dimethylformamide are mixed and stirred for 10 to 16 hours, and then the polyurethane fiber membrane is prepared by an electrospinning process. The process parameters of the electrospinning are: at room temperature, the voltage is 13 to 16 kV, the feed rate is 0.5 to 0.8 ml / h, and the distance from the tip to the collector is 12 to 16 cm.

[0020] The scheme of the present invention adopts polyurethane fiber membrane grafted with heptadecafluorodecyl trimethoxysilane as the outer layer of electric heating gloves, which has the following multiple effects. First, by adding aluminum oxide nanoparticles to the polyurethane fiber membrane, the mechanical strength and wear resistance of the fiber membrane are significantly improved, so that the outer layer of the gloves can withstand the wear and tear of daily use and remain intact. Secondly, the heptadecafluorodecyl trimethoxysilane molecule contains a large number of fluorine atoms, which gives the modified polyurethane fiber membrane excellent hydrophobicity. When the gloves are exposed to a humid environment, the fluorosilane groups on the surface of the fiber membrane can effectively prevent water molecules from penetrating, maintaining the dryness and comfort of the inside of the gloves. At the same time, the unique porous structure of the polyurethane fiber membrane ensures the air permeability of the gloves, and water vapor can be transmitted unidirectionally through the micropores on the fiber membrane, so that the sweat on the hands can be evaporated in time, avoiding the discomfort caused by stuffiness and humidity. In addition, the heptadecafluorodecyl trimethoxysilane grafted polyurethane fiber membrane has both flexibility and wearing comfort. The gloves can fit the curve of the hand tightly without feeling restrained, and have good flexibility, which is very suitable as the outer material of wearable electric heating gloves. In summary, the modified fiber membrane used in the present invention combines multiple advantages such as mechanical properties, moisture resistance, air permeability and flexible wearability, and can meet the actual use requirements of electric heating gloves.

[0021] Furthermore, the heating layer is made of a flexible and highly conductive fiber film.

[0022] Furthermore, the preparation method of the flexible and highly conductive fiber membrane is as follows: in parts by weight, 20 to 28 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 8 to 12 parts of carbon nanotubes and 100 parts of deionized water are ultrasonically dispersed for 20 to 30 minutes to obtain a uniformly mixed solution, which is then evenly poured on a glass plate, and then dried at 35 to 45°C for 2 to 4 hours to obtain a flexible and highly conductive fiber membrane pre-finished product, which is then completely immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 5 to 10 minutes, and then the immersed pre-finished product is washed with deionized water, and finally dried completely in a vacuum drying oven at room temperature to obtain a flexible and highly conductive fiber membrane.

[0023] The flexible conductive film prepared by the present invention has the following characteristics and advantages as the heating layer of the heating gloves: First, the unique structure and strong π-π conjugated interaction between poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and carbon nanotubes are conducive to charge transfer and construct a well-structured conductive network, thereby achieving a higher electrothermal effect; secondly, by optimizing the nanocomposite film with sodium hydroxide aqueous solution, the doping level and carrier concentration can be adjusted, further improving the optimization effect of the electrothermal power; in addition, the conductive film has air permeability and can allow water vapor to pass through, which is crucial for the comfort and performance of flexible conductive materials in wearable applications; finally, the film has good flexibility and wearability, can adapt to different shapes, and can be easily worn on the body or integrated into wearable devices. In summary, the flexible conductive film prepared by the present invention has significant advantages and application potential in terms of high electrothermal effect, sodium hydroxide optimization, air permeability, and flexible wearability.

[0024] Furthermore, the thermally conductive insulating layer is woven from ultra-high molecular weight polyethylene fibers, and the molecular weight thereof is 1 million to 4 million.

[0025] The innovation of the present invention lies in the creative use of ultra-high molecular weight polyethylene fiber as the thermal conductive insulation layer of the electric heating gloves. This design cleverly combines the dual advantages of insulation and thermal conductivity. With its excellent insulation performance, ultra-high molecular weight polyethylene fiber builds a solid barrier for electrical safety, effectively isolates the current, prevents the conductive layer from directly contacting the hand, and ensures the safety of the user. At the same time, its high crystallinity and good orientation give the fiber excellent thermal conductivity, so that heat can be quickly and evenly transferred to the inner surface of the glove along the fiber axis, achieving efficient heating of the hand. In addition, the thermal conductive cloth woven from the fiber adopts a mesh structure design, which not only promotes the natural convection of air, accelerates the dissipation of heat from the hand and the evaporation of sweat, avoids the stuffy discomfort, but also further balances the temperature distribution inside the glove, and improves the uniformity and comfort of heating. In summary, the material selection scheme of the thermal conductive insulation layer of the present invention shows significant advantages in terms of insulation safety, thermal conductivity efficiency and wearing comfort, bringing users a safer, more efficient and comfortable experience in using electric heating gloves.

[0026] Furthermore, the inner layer is woven from flax fibers.

[0027] The innovative inner layer of the linen fiber knitted gloves of the present invention aims to achieve a deep integration and improvement of a series of functions and advantages. Its core goal is to utilize the excellent hygroscopic properties of linen fiber to efficiently absorb and quickly remove sweat produced by the hands, thereby keeping the skin of the hands dry and comfortable, and effectively preventing the discomfort caused by being in a humid environment for a long time. At the same time, the unique woven porous structure of linen fiber gives the inner layer of the gloves excellent air permeability, ensures unimpeded air flow, accelerates the natural dissipation of heat from the hands, significantly reduces the feeling of stuffiness, and improves the overall wearing comfort. Another significant innovation of the present invention is its antibacterial and deodorizing function. The natural antibacterial ingredients contained in linen fiber show strong antibacterial ability, can effectively inhibit the growth and proliferation of bacteria, fundamentally cut off the source of odor caused by bacterial growth, and build a solid protective barrier for hand health. In the pursuit of wearing experience, the present invention is committed to achieving the ultimate optimization of hand feel. The carefully woven inner layer of the linen fiber gloves shows a delicate and soft touch, can fit the skin of the hands tightly, reduce the risk of irritation and allergies, and bring unprecedented comfort. In addition, the present invention also fully considers the durability and practicality of the product. With its excellent toughness, flax fiber shows strong wear resistance after being woven into the inner layer of gloves, which can effectively resist the wear and tear of daily use, significantly extend the service life of gloves, and reduce the replacement frequency, reflecting the in-depth consideration of practicality. Environmental protection and health have always been the unchanging purpose of the present invention. As a natural fiber, flax does not contain any harmful chemicals, is mild and non-irritating to the skin, and is an ideal choice for green health. Choosing the inner layer of flax fiber gloves is not only a manifestation of environmental responsibility, but also a kind of care for one's own health. Finally, the high-density weaving process of flax fiber also gives the inner layer of gloves good warmth retention performance. In the cold winter, this layer of delicate insulation layer can effectively resist the invasion of severe cold, provide warm shelter for the hands, and ensure that the wearer can keep the hands comfortable and warm even in a cold environment. In summary, the inner layer of the flax fiber woven gloves designed by the present invention provides a new solution for hand health and comfort experience by virtue of its multiple excellent properties such as breathable and sweat-absorbent, soft and comfortable, antibacterial and deodorizing, wear-resistant and durable, environmentally friendly and healthy, and warm.

[0028] Furthermore, the three heating temperatures of low temperature, medium temperature and high temperature are 40°C, 48°C and 56°C respectively, and the battery life is 14h, 9h and 6h respectively.

[0029] The heating gloves provided by this design not only meet the personalized warmth needs of different users under different environmental conditions, but also ensure the comfort and safety of use by accurately setting three heating temperatures: low temperature (40℃), medium temperature (48℃), and high temperature (56℃). The low temperature gear is suitable for daily mild cold environments and provides a mild warming effect; the medium temperature gear is suitable for moderate cold or occasions that require more heat supplementation; and the high temperature gear is designed for extreme cold or rapid heating situations to ensure efficient heat output. At the same time, the battery life of each gear is carefully planned as 14h (low temperature), 9h (medium temperature), and 6h (high temperature). This setting not only ensures the convenience of long-term use, but also effectively balances the relationship between heating performance and battery consumption. Users can choose the appropriate temperature gear according to actual needs, and enjoy a lasting warm experience without frequent charging. This intelligent temperature adjustment and battery life optimization not only improves the practicality of the product, but also highlights the humanized considerations of the design, bringing users a more convenient, comfortable and efficient heating solution.

[0030] (3) Beneficial technical effects

[0031] The electrically heated gloves of the present invention achieve unprecedented high-efficiency warmth preservation, safety protection, comfort and durability through a carefully designed multi-layer structure and its synergistic effect. The specific beneficial effects are as follows:

[0032] 1. Significantly improve thermal insulation performance: The gloves of the present invention adopt a double-layer aerogel insulation structure, which gives full play to the thermal insulation advantages of aerogel materials with high porosity and nano-scale pore size. The upper surface is modified with boron nitride-based aerogel fiber woven composite material, and its unique pore structure effectively blocks the conduction and convection of heat. The lower fiber woven polyimide aerogel material further enhances the thermal insulation effect. The two work together to build a double insulation barrier, which is more than 5 times higher than traditional cotton gloves, ensuring that the internal temperature of the gloves is constant in a comfortable range of 18-25°C. Even if working in an extremely cold environment of -40°C for 2 hours, the hands can be kept warm and comfortable.

[0033] 2. High strength and flexibility: The combination of boron nitride and polyimide gives the upper aerogel fiber excellent mechanical strength and toughness. The rigid imide ring in the polyimide molecular chain provides excellent tensile strength and flexural strength. The fiber woven polyimide material used in the lower layer has an elastic modulus of more than 3GPa. The synergistic effect of the two makes the gloves have both the strength of steel and the softness of cotton fabrics, making them flexible, comfortable and durable.

[0034] 3. Ensure safe use: The introduction of nano-hydroxyapatite and magnesium hydroxide flame retardants significantly improves the flame retardant properties of the lower layer of aerogel. When exposed to open flames, the flame retardant reacts quickly to form a heat-insulating and oxygen-blocking protective layer to inhibit the spread of combustion, with an oxygen index of up to 49%. Even at a high temperature of 1200°C, it can maintain a stable shape for up to 30 minutes. At the same time, the inherent insulation of the upper layer of boron nitride fiber can withstand high pressure without breakdown. The synergy of multiple flame-retardant and insulating mechanisms builds a solid safety line for the wearer.

[0035] 4. Excellent moisture and stain resistance: In order to solve the pain point of glove durability, the present invention uses polydimethylsiloxane to hydrophobically modify the upper fiber. The methyl hydrophobic groups on the siloxane molecular chain are firmly fixed on the fiber surface, forming a strong chemical bond with the fiber skeleton. The prepared super hydrophobic surface has a water contact angle of more than 150°, which not only effectively prevents moisture intrusion and avoids the problem of thermal insulation failure caused by aerogel moisture absorption, but also prevents dirt adhesion and has excellent anti-fouling and self-cleaning capabilities.

[0036] 5. Synergy between layers: The electric heating gloves of the present invention adopt a multi-layer composite structure. The optimization and synergy of the materials of each layer comprehensively improve the comprehensive performance of the gloves: the outer layer of fluorosilane modified polyurethane fiber film has high strength, wear resistance and hydrophobic breathable properties, ensuring the durability and comfort of the gloves; the heating layer adopts PEDOT:PSS / CNTs composite conductive film to achieve efficient electric heat conversion and adjustable power, and good breathability and flexibility; the ultra-high molecular weight polyethylene fiber thermal insulation layer achieves efficient heat conduction and breathable perspiration while ensuring safety; the inner layer of flax fiber, with its natural advantages, creates a comfortable, healthy and environmentally friendly skin-friendly layer. The synergistic effect of multiple layers creates an intelligent electric heating glove that integrates high performance, high comfort and high safety.

[0037] 6. Wide application prospects: Based on the above excellent performance, the electric heating gloves of the present invention can be widely used in various extremely cold and harsh environments such as winter outdoor work, high-altitude mountaineering and exploration, and low-temperature cold storage work, providing reliable hand protection and warmth for workers. Previously, these fields have always faced pain points such as poor thermal insulation, low flexibility, and easy moisture absorption and failure of warm gloves. The present invention effectively overcomes the above problems by relying on the double-layer aerogel fiber to synergistically enhance thermal insulation, high strength and flexibility, flame retardancy and moisture resistance.

[0038] In summary, the present invention cleverly utilizes the synergistic effect of the upper and lower layers of aerogel fibers to achieve significant improvements in multiple performance dimensions such as thermal insulation, mechanics, flame retardancy, and moisture resistance. Multifunctional integrated innovation has overcome many pain points of traditional cold-proof gloves and greatly expanded the application scenarios. The present invention has outstanding application value in improving operational safety and efficiency, promoting industrial upgrading, and showing broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic structural diagram of the heating gloves of the present invention.

[0040] Figure 2 It is a cross-sectional view of the heating glove body.

[0041] Figure 3 This is a SEM morphology image of the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane of the outer layer of the glove prepared in Example 1 of the present invention.

[0042] Figure 4 This is a Fourier transform infrared spectrum (FTIR) of the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane of the outer layer of the glove prepared in Example 1 of the present invention.

[0043] Figure 5 This is a cross-sectional SEM morphology image of the surface-modified boron nitride-based aerogel fiber of the upper thermal insulation aerogel layer prepared in Example 1 of the present invention.

[0044] Figure 6 The morphology of water droplets on the surface-modified boron nitride-based aerogel fibers of the upper thermal insulation aerogel layer prepared in Example 1 of the present invention.

[0045] Figure 7 This is a Fourier transform infrared spectrum (FTIR) graph of the surface-modified boron nitride-based aerogel fiber of the upper thermal insulation aerogel layer prepared in Example 1 of the present invention.

[0046] Figure 8 This is a cross-sectional SEM morphology of the thermal insulation and fire-resistant gas gel fiber of the lower thermal insulation aerogel layer prepared in Example 1 of the present invention.

[0047] Fig. 9 This is a morphology picture of the heat insulating and fire resistant gas gel fiber of the lower heat insulating aerogel layer prepared in Example 1 of the present invention after being wound in alcohol for 30 seconds.

[0048] Fig.10 This is a morphology picture of the heat insulating and fire resistant gas gel fiber of the lower heat insulating aerogel layer prepared in Comparative Example 4 of the present invention after being wound in alcohol for 30 seconds.

[0049] Fig.11 This is a physical picture of the thermal insulation and fire-resistant gas gel fiber of the lower thermal insulation aerogel layer prepared in Example 1 of the present invention.

[0050] Fig.12 This is a physical picture of the heating layer of the heating glove prepared in Example 1 of the present invention.

[0051] Fig.13 This is a physical picture of the thermal insulation and fire-resistant gas gel fiber of the lower thermal insulation aerogel layer prepared in Example 1 of the present invention.

[0052] Explanation of the reference numerals: 1. Glove body; 11. Outer layer; 12. Upper thermal insulation aerogel layer; 13. Lower thermal insulation aerogel layer; 14. Heat-generating layer; 15. Thermal conductive insulation layer; 16. Inner layer; 2. Sealing zipper; 3. Power supply slot; 4. Built-in power supply; 6. Temperature control module; 5. Charging port. DETAILED DESCRIPTION

[0053] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0054] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0055] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0056]

[0057]

[0058] Example 1

[0059] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on thermal insulation aerogel, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, an upper thermal insulation aerogel layer 12, a lower thermal insulation aerogel layer 13, a heating layer 14, a thermal conductive insulating layer 15 and an inner layer 16 from the outside to the inside; the outer layer 11, the upper thermal insulation aerogel layer 12, the lower thermal insulation aerogel layer 13, the heating layer 14, the thermal conductive insulating layer 15 and the inner layer 16 are connected together by stitches; a power receiving slot 3 with an open sealing zipper 2 is provided at the back of the hand of the glove body 1, the built-in power supply 4 is placed in the power receiving slot 3 and connected to the heating layer 14 through a wire, a temperature regulating module 6 for adjusting the degree of heating is provided in the wire, the temperature regulating module 6 is set to an off mode and a heating mode, the heating mode has three gears: low temperature, medium temperature and high temperature, the built-in power supply 4 is a rechargeable power supply, and a charging interface 5 for connecting an external power supply is also provided at one end thereof.

[0060] The upper heat-insulating aerogel layer 12 is formed by weaving surface-modified boron nitride-based aerogel fibers through warp and weft; the diameter of the surface-modified boron nitride-based aerogel fibers is 0.2 mm; the thickness is 0.6 mm;

[0061] The surface-modified boron nitride-based aerogel fiber of this embodiment is made of the following raw materials in parts by weight: 20 parts of boron nitride-based aerogel fiber, 150 parts of polyethylene glycol 1000, 20 parts of polydimethylsiloxane, 2 parts of diisopropylbenzene peroxide, and 60 parts of ethanol.

[0062] The lower thermal insulation aerogel layer 13 is formed by weaving thermal insulation and fire-resistant gas gel fibers through warp and weft, and the diameter of the thermal insulation and fire-resistant gas gel is 0.4 mm; the thickness of the lower thermal insulation aerogel layer is 1 mm;

[0063] The heat insulating and fireproof gas gel fiber of this embodiment is made of the following components in mass fraction: 20 parts of 4,4'-diaminodiphenyl ether, 20 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide, 4 parts of nano-hydroxyapatite, and 3 parts of magnesium hydroxide.

[0064] The preparation method of boron nitride-based aerogel fiber in this embodiment is as follows: in parts by weight, 5 parts of boron nitride, 20 parts of 4,4'-diaminodiphenyl ether, 20 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide and 3 parts of triethylamine are mixed and stirred for 2 hours to obtain a boron nitride-based spinning solution, and then the evenly mixed boron nitride-based spinning solution is added to a pump-controlled syringe, followed by pump-controlled extrusion, and a boron nitride-based aerogel fiber pre-finished product is obtained through a freeze spinning process, and then it is freeze-dried and heated to 200°C in a tubular furnace under a nitrogen atmosphere for 30 minutes to complete thermal imidization, and finally the boron nitride-based aerogel fiber is obtained.

[0065] In this embodiment, the outer layer 11 is a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, and its preparation method is: after 3 parts of heptadecafluorodecyltrimethoxysilane and 80 parts of methanol are evenly mixed, 15 parts of polyurethane fiber membrane are completely immersed therein for 10 hours, and then the immersed polyurethane fiber membrane is taken out and dried in a vacuum drying oven at 50°C for 20 hours to obtain the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane.

[0066] The preparation method of the polyurethane fiber membrane in this embodiment is: in parts by weight, 10 parts of polyurethane, 3 parts of aluminum oxide nanoparticles and 80 parts of dimethylformamide are mixed and stirred for 10 hours, and then the polyurethane fiber membrane is prepared by an electrospinning process. The process parameters of the electrospinning are: at room temperature, the voltage is 13 kV, the feed rate is 0.5 ml / h, and the distance from the tip to the collector is 12 cm.

[0067] The preparation method of nano hydroxyapatite in this embodiment is as follows: in parts by weight, 20 parts of 0.2 mol / L calcium nitrate aqueous solution are adjusted to a pH of 9 with 10% ammonia water, and then 15 parts of 0.2 mol / L diammonium hydrogen phosphate aqueous solution are added thereto, and then stirred evenly at room temperature for 24 hours. During the stirring process, 10% ammonia water is required to maintain the pH of the mixed solution at 10. After the stirring is completed, the mixture is filtered, and then the filter residue is washed 3 times with deionized water. Each washing requires that the filter residue be completely submerged with deionized water, and then the washed filter residue is completely dried in a vacuum drying oven at room temperature to finally obtain nano hydroxyapatite.

[0068] The average particle size of the nano-hydroxyapatite in this embodiment is 40 nm.

[0069] In this embodiment, the heating layer 14 is a flexible highly conductive fiber membrane, and its preparation method is as follows: in parts by weight, 20 parts of poly (3, 4-ethylenedioxythiophene) - (polystyrene sulfonic acid), 8 parts of carbon nanotubes and 100 parts of deionized water are ultrasonically dispersed for 20 minutes to obtain a uniformly mixed solution, which is then evenly poured on a glass plate, and then dried at 35°C for 2 hours to obtain a flexible highly conductive fiber membrane pre-finished product, which is then completely immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 5 minutes, and then the immersed pre-finished product is washed with deionized water, and finally dried completely in a vacuum drying oven at room temperature to obtain a flexible highly conductive fiber membrane.

[0070] In this embodiment, the heat-conducting insulating layer 15 is woven from ultra-high molecular weight polyethylene fibers, and the molecular weight thereof is 1 million.

[0071] In this embodiment, the inner layer 16 of the glove is woven from flax fibers.

[0072] In this embodiment, the low temperature heating temperature is set to 40° C. and the battery life is 14 hours.

[0073] Example 2

[0074] See also Figure 1-2The present invention provides a technical solution: a heating glove based on thermal insulation aerogel, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, an upper thermal insulation aerogel layer 12, a lower thermal insulation aerogel layer 13, a heating layer 14, a thermal conductive insulating layer 15 and an inner layer 16 from the outside to the inside; the outer layer 11, the upper thermal insulation aerogel layer 12, the lower thermal insulation aerogel layer 13, the heating layer 14, the thermal conductive insulating layer 15 and the inner layer 16 are connected together by stitches; a power receiving slot 3 with an open sealing zipper 2 is provided at the back of the hand of the glove body 1, the built-in power supply 4 is placed in the power receiving slot 3 and connected to the heating layer 14 through a wire, a temperature regulating module 6 for adjusting the degree of heating is provided in the wire, the temperature regulating module 6 is set to an off mode and a heating mode, the heating mode has three gears: low temperature, medium temperature and high temperature, the built-in power supply 4 is a rechargeable power supply, and a charging interface 5 for connecting an external power supply is also provided at one end thereof.

[0075] The upper heat-insulating aerogel layer 12 is formed by weaving surface-modified boron nitride-based aerogel fibers through warp and weft; the diameter of the surface-modified boron nitride-based aerogel fibers is 0.4 mm; the thickness is 1.3 mm;

[0076] The surface-modified boron nitride-based aerogel fiber of this embodiment is made of the following raw materials in parts by weight: 28 parts of boron nitride-based aerogel fiber, 159 parts of polyethylene glycol 1000, 23 parts of polydimethylsiloxane, 2.3 parts of diisopropylbenzene peroxide, and 60 parts of ethanol.

[0077] The lower heat-insulating aerogel layer 13 is formed by weaving heat-insulating and fire-resistant gas gel fibers through warp and weft, and the diameter of the heat-insulating and fire-resistant gas gel is 0.6 mm and the thickness is 1.9 mm;

[0078] The heat insulating and fireproof gas gel fiber of this embodiment is made of the following components in mass fraction: 28 parts of 4,4'-diaminodiphenyl ether, 28 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide, 5 parts of nano-hydroxyapatite, and 4 parts of magnesium hydroxide.

[0079] The preparation method of boron nitride-based aerogel fiber in this embodiment is as follows: in parts by weight, 7 parts of boron nitride, 25 parts of 4,4'-diaminodiphenyl ether, 25 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide and 4 parts of triethylamine are mixed and stirred for 3 hours to obtain a boron nitride-based spinning solution, and then the evenly mixed boron nitride-based spinning solution is added to a pump-controlled syringe, followed by pump-controlled extrusion, and a boron nitride-based aerogel fiber pre-finished product is obtained through a freeze spinning process, and then it is freeze-dried and heated to 220°C in a tubular furnace under a nitrogen atmosphere for 35 minutes to complete thermal imidization, and finally the boron nitride-based aerogel fiber is obtained.

[0080] In this embodiment, the outer layer 11 is a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, and its preparation method is: after 4 parts of heptadecafluorodecyltrimethoxysilane and 85 parts of methanol are evenly mixed, 20 parts of polyurethane fiber membranes are completely immersed therein for 12 hours, and then the immersed polyurethane fiber membrane is taken out and dried in a vacuum drying oven at 52°C for 22 hours to obtain the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane.

[0081] The preparation method of the polyurethane fiber membrane in this embodiment is: in parts by weight, 12 parts of polyurethane, 4 parts of aluminum oxide nanoparticles and 90 parts of dimethylformamide are mixed and stirred for 12 hours, and then the polyurethane fiber membrane is prepared by an electrospinning process. The process parameters of the electrospinning are: at room temperature, the voltage is 14kV, the feed rate is 0.6ml / h, and the distance from the tip to the collector is 13cm.

[0082] The preparation method of nano hydroxyapatite in this embodiment is as follows: in parts by weight, 25 parts of 0.2 mol / L calcium nitrate aqueous solution are adjusted to a pH of 10 with 10% ammonia water, and then 18 parts of 0.2 mol / L diammonium hydrogen phosphate aqueous solution are added thereto, and then stirred evenly at room temperature for 28 hours. During the stirring process, 10% ammonia water is required to maintain the pH of the mixed solution at 10. After the stirring is completed, the mixture is filtered, and then the filter residue is washed 3 times with deionized water. Each washing requires that the filter residue be completely submerged with deionized water, and then the washed filter residue is completely dried in a vacuum drying oven at room temperature to finally obtain nano hydroxyapatite.

[0083] The average particle size of the nano-hydroxyapatite in this embodiment is 50 nm.

[0084] In this embodiment, the heating layer 14 is a flexible highly conductive fiber membrane, and its preparation method is as follows: in parts by weight, 22 parts of poly (3, 4-ethylenedioxythiophene) - (polystyrene sulfonic acid), 9 parts of carbon nanotubes and 100 parts of deionized water are ultrasonically dispersed for 22 minutes to obtain a uniformly mixed solution, which is then evenly poured on a glass plate and then dried at 38°C for 3 hours to obtain a flexible highly conductive fiber membrane pre-finished product, which is then completely immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 6 minutes, and then the immersed pre-finished product is washed with deionized water, and finally dried completely in a vacuum drying oven at room temperature to obtain a flexible highly conductive fiber membrane.

[0085] In this embodiment, the heat-conducting insulating layer 15 is woven from ultra-high molecular weight polyethylene fibers, and the molecular weight thereof is 2 million.

[0086] In this embodiment, the inner layer 16 of the glove is woven from flax fibers.

[0087] In this embodiment, the medium temperature heating temperature is set to 48° C. and the battery life is 9 hours.

[0088] Example 3

[0089] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on thermal insulation aerogel, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, an upper thermal insulation aerogel layer 12, a lower thermal insulation aerogel layer 13, a heating layer 14, a thermal conductive insulating layer 15 and an inner layer 16 from the outside to the inside; the outer layer 11, the upper thermal insulation aerogel layer 12, the lower thermal insulation aerogel layer 13, the heating layer 14, the thermal conductive insulating layer 15 and the inner layer 16 are connected together by stitches; a power receiving slot 3 with an open sealing zipper 2 is provided at the back of the hand of the glove body 1, the built-in power supply 4 is placed in the power receiving slot 3 and connected to the heating layer 14 through a wire, a temperature regulating module 6 for adjusting the degree of heating is provided in the wire, the temperature regulating module 6 is set to an off mode and a heating mode, the heating mode has three gears: low temperature, medium temperature and high temperature, the built-in power supply 4 is a rechargeable power supply, and a charging interface 5 for connecting an external power supply is also provided at one end thereof.

[0090] In this embodiment, the upper heat-insulating aerogel layer 12 is formed by weaving surface-modified boron nitride-based aerogel fibers through warp and weft; the diameter of the surface-modified boron nitride-based aerogel fibers is 0.8 mm; and the thickness is 2.6 mm.

[0091] The surface-modified boron nitride-based aerogel fiber of this embodiment is made of the following raw materials in parts by weight: 35 parts of boron nitride-based aerogel fiber, 168 parts of polyethylene glycol 1000, 26 parts of polydimethylsiloxane, 2.6 parts of diisopropylbenzene peroxide, and 60 parts of ethanol.

[0092] In this embodiment, the lower heat insulating aerogel layer 13 is formed by weaving heat insulating and fire retardant gas gel fibers through warp and weft, and the diameter of the heat insulating and fire retardant gas gel is 1 mm and the thickness is 3 mm.

[0093] The heat insulating and fireproof gas gel fiber of this embodiment is made of the following components in mass fraction: 35 parts of 4,4'-diaminodiphenyl ether, 35 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide, 6 parts of nano-hydroxyapatite, and 6 parts of magnesium hydroxide.

[0094] The preparation method of boron nitride-based aerogel fiber in this embodiment is as follows: in parts by weight, 10 parts of boron nitride, 40 parts of 4,4'-diaminodiphenyl ether, 40 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide and 5 parts of triethylamine are mixed and stirred for 3 hours to obtain a boron nitride-based spinning solution, and then the evenly mixed boron nitride-based spinning solution is added to a pump-controlled syringe, followed by pump-controlled extrusion, and a boron nitride-based aerogel fiber pre-finished product is obtained through a freeze spinning process, and then it is freeze-dried and heated to 280°C in a tubular furnace under a nitrogen atmosphere for 40 minutes to complete thermal imidization, and finally the boron nitride-based aerogel fiber is obtained.

[0095] In this embodiment, the outer layer 11 is a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, and its preparation method is: after 5 parts of heptadecafluorodecyltrimethoxysilane and 95 parts of methanol are evenly mixed, 23 parts of polyurethane fiber membrane are completely immersed therein for 14 hours, and then the immersed polyurethane fiber membrane is taken out and dried in a vacuum drying oven at 58°C for 26 hours to obtain the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane.

[0096] The preparation method of the polyurethane fiber membrane in this embodiment is as follows: 16 parts of polyurethane, 7 parts of aluminum oxide nanoparticles and 110 parts of dimethylformamide are mixed by weight and stirred for 14 hours, and then the polyurethane fiber membrane is prepared by an electrospinning process. The process parameters of the electrospinning are: at room temperature, the voltage is 15 kV, the feed rate is 0.7 ml / h, and the distance from the tip to the collector is 14 cm.

[0097] The preparation method of nano hydroxyapatite in this embodiment is as follows: in parts by weight, 35 parts of 0.2 mol / L calcium nitrate aqueous solution are adjusted to a pH of 10 with 10% ammonia water, and then 20 parts of 0.2 mol / L diammonium hydrogen phosphate aqueous solution are added thereto, and then stirred evenly at room temperature for 32 hours. During the stirring process, 10% ammonia water is required to maintain the pH of the mixed solution at 10. After the stirring is completed, the mixture is filtered, and then the filter residue is washed 3 times with deionized water. Each washing requires that the filter residue be completely submerged with deionized water, and then the washed filter residue is completely dried in a vacuum drying oven at room temperature to finally obtain nano hydroxyapatite.

[0098] The average particle size of the nano-hydroxyapatite in this embodiment is 70 nm.

[0099] In this embodiment, the heating layer 14 is a flexible highly conductive fiber membrane, and its preparation method is as follows: in parts by weight, 26 parts of poly (3, 4-ethylenedioxythiophene) - (polystyrene sulfonic acid), 10 parts of carbon nanotubes and 100 parts of deionized water are ultrasonically dispersed for 28 minutes to obtain a uniformly mixed solution, which is then evenly poured on a glass plate, and then dried at 40°C for 3 hours to obtain a flexible highly conductive fiber membrane pre-finished product, which is then completely immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 8 minutes, and then the immersed pre-finished product is washed with deionized water, and finally dried completely in a vacuum drying oven at room temperature to obtain a flexible highly conductive fiber membrane.

[0100] In this embodiment, the heat-conducting insulating layer 15 is woven from ultra-high molecular weight polyethylene fibers, and the molecular weight thereof is 3 million.

[0101] In this embodiment, the inner layer 16 of the glove is woven from flax fibers.

[0102] In this embodiment, the medium temperature heating temperature is set to 40° C. and the battery life is 9 hours.

[0103] Example 4

[0104] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on thermal insulation aerogel, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, an upper thermal insulation aerogel layer 12, a lower thermal insulation aerogel layer 13, a heating layer 14, a thermal conductive insulating layer 15 and an inner layer 16 from the outside to the inside; the outer layer 11, the upper thermal insulation aerogel layer 12, the lower thermal insulation aerogel layer 13, the heating layer 14, the thermal conductive insulating layer 15 and the inner layer 16 are connected together by stitches; a power receiving slot 3 with an open sealing zipper 2 is provided at the back of the hand of the glove body 1, the built-in power supply 4 is placed in the power receiving slot 3 and connected to the heating layer 14 through a wire, a temperature regulating module 6 for adjusting the degree of heating is provided in the wire, the temperature regulating module 6 is set to an off mode and a heating mode, the heating mode has three gears: low temperature, medium temperature and high temperature, the built-in power supply 4 is a rechargeable power supply, and a charging interface 5 for connecting an external power supply is also provided at one end thereof.

[0105] In this embodiment, the upper heat-insulating aerogel layer 12 is formed by weaving surface-modified boron nitride-based aerogel fibers through warp and weft; the diameter of the surface-modified boron nitride-based aerogel fibers is 1 mm; and the thickness is 3 mm.

[0106] The surface-modified boron nitride-based aerogel fiber of this embodiment is made of the following raw materials in parts by weight: 45 parts of boron nitride-based aerogel fiber, 180 parts of polyethylene glycol 1000, 30 parts of polydimethylsiloxane, 3 parts of diisopropylbenzene peroxide, and 60 parts of ethanol.

[0107] In this embodiment, the lower heat insulating aerogel layer 13 is formed by weaving heat insulating and fire retardant gas gel fibers through warp and weft. The diameter of the heat insulating and fire retardant gas gel is 1.2 mm and the thickness is 4 mm.

[0108] The surface-modified boron nitride-based aerogel fiber of this embodiment is made of the following raw materials in parts by weight: 45 parts of boron nitride-based aerogel fiber, 180 parts of polyethylene glycol 1000, 30 parts of polydimethylsiloxane, 3 parts of diisopropylbenzene peroxide, and 60 parts of ethanol.

[0109] The preparation method of boron nitride-based aerogel fiber in this embodiment is as follows: in parts by weight, 12 parts of boron nitride, 45 parts of 4,4'-diaminodiphenyl ether, 45 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide and 6 parts of triethylamine are mixed and stirred for 4 hours to obtain a boron nitride-based spinning solution, and then the evenly mixed boron nitride-based spinning solution is added to a pump-controlled syringe, followed by pump-controlled extrusion, and a boron nitride-based aerogel fiber pre-finished product is obtained through a freeze spinning process, and then it is freeze-dried and heated to 300°C in a tubular furnace under a nitrogen atmosphere for 45 minutes to complete thermal imidization, and finally the boron nitride-based aerogel fiber is obtained.

[0110] In this embodiment, the outer layer 11 is a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, and its preparation method is: after 6 parts of heptadecafluorodecyltrimethoxysilane and 100 parts of methanol are evenly mixed, 25 parts of polyurethane fiber membranes are completely immersed therein for 16 hours, and then the immersed polyurethane fiber membrane is taken out and dried in a vacuum drying oven at 60°C for 28 hours to obtain the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane.

[0111] The preparation method of the polyurethane fiber membrane in this embodiment is as follows: 18 parts of polyurethane, 8 parts of aluminum oxide nanoparticles and 120 parts of dimethylformamide are mixed by weight and stirred for 16 hours, and then the polyurethane fiber membrane is prepared by an electrospinning process. The process parameters of the electrospinning are: at room temperature, the voltage is 16 kV, the feed rate is 0.8 ml / h, and the distance from the tip to the collector is 16 cm.

[0112] The preparation method of nano hydroxyapatite in this embodiment is as follows: by weight, 40 parts of 0.2 mol / L calcium nitrate aqueous solution are adjusted to a pH of 11 with 10% ammonia water, and then 25 parts of 0.2 mol / L diammonium hydrogen phosphate aqueous solution are added thereto, and then stirred evenly at room temperature for 36 hours. During the stirring process, 10% ammonia water is required to maintain the pH of the mixed solution at 10. After the stirring is completed, the mixture is filtered, and then the filter residue is washed 3 times with deionized water. Each washing requires that the filter residue be completely submerged with deionized water, and then the washed filter residue is completely dried in a vacuum drying oven at room temperature to finally obtain nano hydroxyapatite.

[0113] The average particle size of the nano-hydroxyapatite in this embodiment is 80 nm.

[0114] In this embodiment, the heating layer 14 is a flexible highly conductive fiber membrane, and its preparation method is as follows: in parts by weight, 28 parts of poly (3, 4-ethylenedioxythiophene) - (polystyrene sulfonic acid), 12 parts of carbon nanotubes and 100 parts of deionized water are ultrasonically dispersed for 30 minutes to obtain a uniformly mixed solution, which is then evenly poured on a glass plate, and then dried at 45 ° C for 4 hours to obtain a flexible highly conductive fiber membrane pre-finished product, which is then completely immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 10 minutes, and then the immersed pre-finished product is washed with deionized water, and finally dried completely in a vacuum drying oven at room temperature to obtain a flexible highly conductive fiber membrane.

[0115] In this embodiment, the thermally conductive insulating layer 15 is woven from ultra-high molecular weight polyethylene fibers, and the molecular weight thereof is 4 million.

[0116] In this embodiment, the inner layer 16 of the glove is woven from flax fibers.

[0117] In this embodiment, the third high temperature heating temperature is set to 56° C., and the battery life is 6 hours.

[0118] Example 5

[0119] It is basically the same as Example 1, except that the number of boron nitride-based aerogel fibers used to prepare the upper aerogel insulation layer is 45 parts.

[0120] Comparative Example 1

[0121] It is basically the same as Example 1, except that no boron nitride is added to the surface of the boron nitride-based aerogel fibers of the upper aerogel insulation layer.

[0122] Comparative Example 2

[0123] The method is basically the same as Example 1, except that the surface of the boron nitride-based aerogel fiber of the upper aerogel insulation layer is not surface-modified with polydimethylsiloxane.

[0124] Comparative Example 3

[0125] It is basically the same as Example 1, except that nano-hydroxyapatite is not added to the lower thermal insulation aerogel layer.

[0126] Comparative Example 4

[0127] The method is basically the same as Example 1, except that magnesium hydroxide is not added to the lower thermal insulation aerogel layer.

[0128] Characterization Tests:

[0129] Figure 3The SEM morphology of the outer layer of the glove prepared in Example 1 of the present invention, the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, can be concluded that the surface of the outer layer of the glove presents a uniform fiber membrane structure, and there is no obvious unevenness or clot phenomenon. The outer layer of the glove prepared in Example 1 of the present invention, the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, is reasonable, has a uniform surface morphology, good fiber membrane adhesion, and the fiber membrane morphology is smooth and uniform. These characteristics indicate that the outer layer of the glove can effectively provide a protective function and has potential application prospects.

[0130] In this study, Fourier transform infrared spectroscopy (FTIR) was used to deeply explore the surface chemical composition of the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane prepared in Example 1. Figure 4 As shown in the figure, the heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane and the polyurethane fiber membrane exhibited multiple characteristic peaks in the spectrum, which corresponded to the COC bond (1108cm -1 ), carbonyl C=O (1735cm -1 ), methylene-CH 2 -(2923cm -1 and 2854cm -1 ) and hydroxyl -OH (3434cm -1 ) stretching vibration, after grafting with heptadecafluorodecyltrimethoxysilane, a new peak at 1224 cm -1 The characteristic peak of CF bond proves that heptadecafluorodecyltrimethoxysilane has been successfully grafted onto the surface of polyurethane fiber membrane, thus achieving the expected chemical modification.

[0131] Figure 5 This is a SEM morphology of the cross section of the surface-modified boron nitride-based aerogel fiber of the upper thermal insulation aerogel layer prepared in Example 1 of the present invention. From the figure, it can be observed that there is a uniformly distributed microscopic pore structure in the fiber cross section. These pores have a small size and a uniform distribution, which can provide excellent thermal insulation performance.

[0132] Figure 6 The morphology of water droplets on the surface-modified boron nitride-based aerogel fibers of the upper insulating aerogel layer prepared in Example 1 of the present invention. It can be observed from the figure that the water droplets on the surface of the aerogel fibers present a smooth shape, and there is no obvious fusion or penetration between the water droplets. This shows that the surface of the aerogel fiber has a certain hydrophobicity, so that the water droplets form spheres on the surface, and it is not easy to penetrate into the fiber, which further proves the hydrophobicity of the surface of the aerogel fiber and is not easy to penetrate into the fiber. These characteristics show that the aerogel layer can effectively block water penetration and has potential application prospects, especially in the field of waterproofing and moisture-proofing. It has a wide range of application value.

[0133] Figure 7 The results of Fourier transform infrared spectroscopy (FTIR) analysis of the surface-modified boron nitride-based aerogel fiber in the upper insulating aerogel layer prepared in Example 1 of the present invention are shown. In the framework of FTIR spectral analysis, the polyimide (PI) aerogel fiber shows two significant characteristic absorption peaks, located at 1711cm-1 and 1773cm-1, respectively. These two peaks correspond precisely to the characteristic modes of symmetric and asymmetric stretching vibrations of the C=O group in the molecular skeleton. In addition, an absorption peak appears at 805cm-1, which belongs to the out-of-plane bending vibration of BNB. Its appearance directly and clearly proves the effective incorporation and good dispersion of BN nanosheets in the PI matrix, and provides conclusive spectroscopic evidence for the successful composite of BN nanosheets and PI matrix. The CH vibration peak at 2923cm-1 in the infrared spectrum is a direct spectral sign of the successful embedding of the PEG molecular segment into the aerogel fiber structure, and 745cm-1 comes from the Si-O bond of the surface-modified polydimethylsiloxane. This discovery not only verifies the effective compounding of PEG components, the high efficiency of the preparation process of surface-modified boron nitride-based aerogel fibers and the successful preparation of the final product, but also demonstrates the rationality of the design of the composite system and the feasibility of its implementation.

[0134] Figure 8 This is a cross-sectional SEM morphology of the thermal insulation and flame retardant gas gel fiber of the lower thermal insulation aerogel layer prepared in Example 1 of the present invention. From the figure, its unique nanoporous network structure can be seen. This structural feature significantly enhances the thermal insulation effect and flame retardant ability of the fiber. Specifically, the highly dispersed and dense nanopores inside the aerogel fiber effectively hinder heat conduction and convection.

[0135] Fig. 9 It shows that the heat-insulating and flame-retardant gas gel fiber used in the lower heat-insulating aerogel layer prepared in Example 1 of the present invention did not curl or deform after burning in the flame of an alcohol lamp for 30 seconds, which proves that the aerogel fiber has good flame-retardant properties and can maintain a stable shape in the flame, playing a role in heat insulation and flame retardancy. In contrast, Fig.10 The aerogel fiber used in the lower insulating aerogel layer prepared in Comparative Example 4 underwent obvious curling and deformation after being burned by an alcohol lamp flame under the same conditions for 30 seconds, indicating that the performance of this aerogel fiber is unstable in high-temperature flames and does not have sufficient flame retardant properties.

[0136] Fig.12 The actual image of the aerogel layer under the heating glove prepared in Example 1 of the present invention is shown. Through the folding and bending test, it is proved that the layer has good flexibility and can adapt to various movements of the hand without being easily damaged; Fig.12 A physical picture of the heating layer of the heating gloves was also shown, proving the successful preparation of the heating layer; Fig.13The actual pictures of the heating layer and the lower aerogel layer of the heating gloves prepared in Example 1 of the present invention are simultaneously shown, which intuitively proves the successful preparation and assembly of these two key functional layers and lays the foundation for the subsequent overall assembly.

[0137] Performance Test:

[0138] Thermal conductivity is one of the important indicators in the application of thermal insulation aerogel. The thermal conductivity of the upper and lower thermal insulation aerogel layers was tested using the TPS 2500S hot plate thermal constant analyzer (produced by Swedish Hot Plate Co., Ltd.). Before the test, the flatness and defect-freeness of the sample were ensured, and the equipment was calibrated as required. During the test, the sample was placed tightly on the hot plate probe of the analyzer, and the diffusion process of heat in the sample was recorded by the transient thermal pulse method. Subsequently, the data were analyzed using software to obtain the thermal conductivity values ​​of the two layers of aerogel. The entire test process strictly followed the operating procedures to ensure the accuracy and reliability of the results, providing an important basis for the performance evaluation and application research of the material.

[0139] Mechanical properties: The mechanical properties of the upper and lower thermal insulation aerogel layers were tested using an electronic universal testing instrument (SANS UTM2102, China). During the test, the sample was precisely installed in the fixture of the testing machine, the appropriate stretching rate was set, and then the instrument was started to stretch until the sample broke. By recording and analyzing the force-displacement curve during the stretching process, the key mechanical performance indicators of the tensile strength and elongation of the two layers of aerogel were evaluated.

[0140] Hydrophobicity: The hydrophobicity of the upper insulating aerogel layer was tested at room temperature using the DSA-100S optical contact angle system (OSA200, Germany). By gently placing a small amount of water droplets on the sample surface and using the system's high-precision camera to capture the shape of the water droplets at the moment of contact with the sample, the water contact angle was measured. This parameter directly reflects the hydrophobicity of the aerogel layer surface and provides key data for evaluating its waterproof and moisture-proof capabilities.

[0141] Flame retardant properties: According to ASTM standard D2863, the flame retardancy of the lower insulating aerogel layer was tested using an oxygen index meter (JF-3, China) to evaluate its limited oxygen index (LOI). During the test, by adjusting the concentration of oxygen in the mixed gas and observing the continuous burning time or whether the sample ignites under specific conditions, the minimum oxygen concentration required for the aerogel layer to maintain combustion, i.e., the LOI value, was determined. This index directly reflects the flame retardant properties of the material and is of great significance for evaluating its safety in fire.

[0142] The properties of the thermal insulation aerogel layers of Examples 1 to 5 and Comparative Examples 1 to 2 are summarized in Table 2; the properties of the thermal insulation aerogel layers of Examples 1 to 5 and Comparative Examples 3 to 4 are summarized in Table 3

[0143] Table 2 Performance of thermal insulation aerogel layers in Examples 1 to 5 and Comparative Examples 1 to 2

[0144]

[0145] Table 3 Performance summary of thermal insulation aerogel layer in Examples 1 to 5 and Comparative Examples 3 to 4

[0146]

[0147]

[0148] The main difference between Comparative Example 1 and Example 1 is whether boron nitride is added to the surface of the boron nitride-based aerogel fibers of the upper aerogel insulation layer. It can be seen from Table 2 that the addition of boron nitride significantly increases the tensile strength of the upper aerogel insulation layer. This is because the addition of boron nitride significantly improves the tensile strength and overall mechanical properties of the upper aerogel insulation layer by enhancing material strength, optimizing microstructure, promoting interface bonding and possible chemical cross-linking.

[0149] The main difference between Comparative Example 2 and Example 1 is whether the surface of the boron nitride-based aerogel fiber of the upper aerogel insulation layer is surface-modified with polydimethylsiloxane. It can be seen from Table 2 that surface modification can significantly improve the hydrophobic properties of the boron nitride-based aerogel fiber. This is because the low surface energy characteristics of polydimethylsiloxane effectively reduce the interaction force between the fiber surface and water molecules, thereby enhancing the waterproof and moisture-proof ability of the fiber.

[0150] The main difference between Comparative Example 3 and Example 1 is whether nanohydroxyapatite is added to the thermal insulation aerogel layer. From the data analysis of Table 3, it can be seen that the addition of nanohydroxyapatite not only significantly improves the flame retardant properties of the thermal insulation aerogel layer, making it more stable under high temperature environment, but also unexpectedly enhances the tensile strength and thermal insulation properties of the material. This multiple enhancement effect can be attributed to the unique physical and chemical properties of nanohydroxyapatite, which can act as an effective flame retardant to prevent flame propagation, while its nanostructure helps to enhance the mechanical properties and thermal insulation efficiency of the material.

[0151] In the comparative study between Comparative Example 4 and Example 1, a significant difference is whether magnesium hydroxide is introduced into the insulating aerogel layer. Through a careful analysis of the data in Table 3, we can observe that the addition of magnesium hydroxide has a multi-faceted positive effect on the insulating aerogel layer. First, it greatly enhances the flame retardant properties of the material, so that the layer can maintain a higher stability when exposed to high temperature or fire source, effectively suppressing the spread of fire. Furthermore, the introduction of magnesium hydroxide also unexpectedly promotes the improvement of tensile strength and thermal insulation properties of the insulating aerogel layer. This unexpected double enhancement effect can be attributed to a series of superior properties of magnesium hydroxide itself. As an efficient flame retardant, magnesium hydroxide absorbs a large amount of heat and releases water vapor during decomposition, all of which help to slow down the combustion rate and reduce heat transfer. At the same time, the nanoscale particles in its microstructure may promote the optimization of the microstructure inside the material, thereby enhancing the mechanical properties and thermal insulation capacity of the material. In summary, the application of magnesium hydroxide in the thermal insulation aerogel layer not only improves its flame retardant properties, but also unexpectedly strengthens the mechanical and thermal insulation properties of the material, providing a new idea for the performance optimization of thermal insulation aerogel materials.

[0152] In addition, the LOI of the lower thermal insulation aerogel layer prepared by the present invention is 47.9-49.1%, which is much higher than commercial aramid fabric (30.6%) and polyimide fabric (34.8%), proving that the lower thermal insulation aerogel layer has excellent flame retardant properties.

[0153] The electric heating gloves of the present invention use the cooperation of the upper and lower double-layer heat-insulating aerogel layers and special materials to construct a comprehensive protection system that integrates heat preservation, heat insulation, flame retardancy, lightness, flexibility and durability. The upper layer strengthens heat insulation and mechanical strength, and is resistant to moisture and stains; the lower layer builds a heat insulation barrier and combines flame retardant ingredients to improve safety. The inner and outer layers work together to achieve multiple protections, taking into account both comfort and safety, and provide an excellent solution for electric heating gloves.

[0154] In summary, the electric heating gloves of the present invention integrate multi-layer innovative design, and are highly efficient in keeping warm, safe and protective, and comfortable and durable. The outer layer is wear-resistant, waterproof and breathable; the upper insulating aerogel layer is strong and insulated, resistant to moisture and stains; the lower insulating aerogel layer is highly efficient in insulating and flame-retardant; the heating layer is intelligently thermostatic, comfortable and dry; the thermal conductive insulation layer is safe in thermal conductivity, breathable and not stuffy; the inner layer of flax fiber is natural, healthy, comfortable and antibacterial. All layers work together to comprehensively improve performance and provide an excellent solution for working in cold environments. .

[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A heating glove based on thermal insulation aerogel, characterized in that: The glove body (1) comprises an outer layer (11), an upper heat-insulating aerogel layer (12), a lower heat-insulating aerogel layer (13), a heating layer (14), a heat-conducting insulating layer (15) and an inner layer (16) from the outside to the inside; the outer layer (11), the upper heat-insulating aerogel layer (12), the lower heat-insulating aerogel layer (13), the heating layer (14), the heat-conducting insulating layer (15) and the inner layer (16) are all connected together by stitches; a power supply receiving slot (3) containing an open-type sealing zipper (2) is provided at the back of the hand of the glove body (1); a built-in power supply (4) is placed in the power supply receiving slot (3) and connected to the heating layer (14) through a wire; a temperature regulating module (6) for regulating the degree of heating is provided in the wire; the temperature regulating module (6) is provided with an off mode and a heating mode; the heating mode has three gears: low temperature, medium temperature and high temperature; the built-in power supply (4) is a rechargeable power supply, and one end of the built-in power supply is also provided with a charging interface (5) for connecting to an external power supply; The upper heat-insulating aerogel layer (12) is formed by weaving surface-modified boron nitride-based aerogel fibers through warp and weft; the diameter of the surface-modified boron nitride-based aerogel fibers is 0.2 to 1 mm; the thickness of the upper heat-insulating aerogel layer is 0.6 to 3 mm; The surface modified boron nitride-based aerogel fiber is made of the following raw materials in parts by weight: 20 to 45 parts of boron nitride-based aerogel fiber, 150 to 180 parts of polyethylene glycol 1000, 20 to 30 parts of polydimethylsiloxane, 2 to 3 parts of dicumyl peroxide, and 60 parts of ethanol; the mass ratio of the polydimethylsiloxane to dicumyl peroxide is 10:1; The lower thermal insulation aerogel layer (13) is formed by weaving thermal insulation and fire-resistant gas gel fibers through warp and weft, and the diameter of the thermal insulation and fire-resistant gas gel is 0.4-1.2 mm; the thickness of the lower thermal insulation aerogel layer is 1-4 mm; The heat-insulating and flame-retardant gas gel fiber is made of the following components by weight: 20 to 45 parts of 4,4'-diaminodiphenyl ether, 20 to 45 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide, 4 to 8 parts of nano-hydroxyapatite, and 3 to 8 parts of magnesium hydroxide; the mass ratio of the 4,4'-diaminodiphenyl ether to the 3,3',4,4'-biphenyltetracarboxylic dianhydride is 1:

1.

2. A heating glove based on thermal insulation aerogel as claimed in claim 1, characterized in that: The preparation method of the boron nitride-based aerogel fiber is as follows: by weight, 5 to 12 parts of boron nitride, 20 to 45 parts of 4,4'-diaminodiphenyl ether, 20 to 45 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 500 parts of N,N-dimethylacetamide and 3 to 6 parts of triethylamine are mixed and stirred for 2 to 4 hours to obtain a boron nitride-based spinning solution, and then the uniformly mixed boron nitride-based spinning solution is added to a pump-controlled syringe, and then pump-controlled extrusion is adopted to obtain a boron nitride-based aerogel fiber pre-product by a freeze spinning process, and then the pre-product is freeze-dried and heated to 200 to 300° C. in a tubular furnace under a nitrogen atmosphere for 30 to 45 minutes to complete thermal imidization, and finally the boron nitride-based aerogel fiber is obtained; the mass ratio of the 4,4'-diaminodiphenyl ether to the 3,3',4,4'-biphenyltetracarboxylic dianhydride is 1:1; 3. The heating glove based on thermal insulation aerogel according to claim 1, characterized in that: The outer layer (11) is a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane, and the preparation method thereof is as follows: 3 to 6 parts of heptadecafluorodecyltrimethoxysilane and 80 to 100 parts of methanol are uniformly mixed, and 15 to 25 parts of polyurethane fiber membrane are completely immersed therein. The immersion time is 10 to 16 hours, and then the impregnated polyurethane fiber membrane is taken out and dried in a vacuum drying oven at 50 to 60° C. for 20 to 28 hours to obtain a heptadecafluorodecyltrimethoxysilane grafted polyurethane fiber membrane.

4. A heating glove based on thermal insulation aerogel as claimed in claim 3, characterized in that: The preparation method of the polyurethane fiber membrane is as follows: by weight, 10 to 18 parts of polyurethane, 3 to 8 parts of aluminum oxide nanoparticles and 80 to 120 parts of dimethylformamide are mixed and stirred for 10 to 16 hours, and then the polyurethane fiber membrane is prepared by an electrospinning process. The process parameters of the electrospinning are: at room temperature, the voltage is 13 to 16 kV, the feed rate is 0.5 to 0.8 ml / h, and the distance from the tip to the collector is 12 to 16 cm.

5. The heating glove based on thermal insulation aerogel according to claim 1, characterized in that: The preparation method of the nano hydroxyapatite is as follows: by weight, 20 to 40 parts of a 0.2 mol / L calcium nitrate aqueous solution are adjusted to a pH of 9 to 11 with 10% ammonia water by mass, and then 15 to 25 parts of a 0.2 mol / L diammonium hydrogen phosphate aqueous solution are added thereto, and then stirred evenly at room temperature for 24 to 36 hours. During the stirring process, 10% ammonia water by mass is required to maintain the pH of the mixed solution at 10. After the stirring is completed, the mixture is filtered, and then the filter residue is washed 3 times with deionized water, and each washing needs to completely submerge the filter residue with deionized water, and then the washed filter residue is completely dried in a vacuum drying oven at room temperature to finally obtain the nano hydroxyapatite.

6. A heating glove based on thermal insulation aerogel according to claim 1 or 5, characterized in that: The average particle size of the nano-hydroxyapatite is 40-80nm.

7. The heating glove based on thermal insulation aerogel according to claim 1, characterized in that: The heating layer (14) is a flexible highly conductive fiber membrane, and its preparation method is as follows: by weight, 20 to 28 parts of poly (3, 4-ethylenedioxythiophene) -poly (styrene sulfonic acid), 8 to 12 parts of carbon nanotubes and 100 parts of deionized water are ultrasonically dispersed for 20 to 30 minutes to obtain a uniformly mixed solution, which is then uniformly poured on a glass plate, and then dried at 35 to 45°C for 2 to 4 hours to obtain a flexible highly conductive fiber membrane pre-finished product, which is then completely immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 5 to 10 minutes, and then the immersed pre-finished product is washed with deionized water, and finally dried completely in a vacuum drying oven at room temperature to obtain a flexible highly conductive fiber membrane.

8. The heating glove based on thermal insulation aerogel according to claim 1, characterized in that: The heat-conducting insulating layer (15) is woven from ultra-high molecular weight polyethylene fibers, and the molecular weight thereof is 1 million to 4 million.

9. The heating glove based on thermal insulation aerogel according to claim 1, characterized in that: The inner layer (16) is woven from flax fibers.

10. The heating glove based on thermal insulation aerogel according to claim 1, characterized in that: The three heating temperatures of low temperature, medium temperature and high temperature are 40°C, 48°C and 56°C respectively, and the battery life is 14h, 9h and 6h respectively.

Citation Information

Patent Citations

  • Cold-proof electric heating glove

    CN116807113A

  • Aerogel electric heating glove

    CN212212820U

  • Novel aerogel heat insulation film

    CN111777958A

  • Preparation method of flexible protection structure with heat insulation, flame retardance and self-cleaning performance

    CN113756100A